Sanad as an Epistemology of Hadith Validation: The Perceptions of Upper Secondary School Teachers in Kediri City - Khamim; Lu'lu'atus Saniyya Fadhila (LPPM UIN Syekh Wasil Kediri, 2026)
This study examines Madrasah Aliyah teachers’ perceptions of the role of sanad in hadith validation and its implications for hadith learning in Kediri. Sanad is not merely a technical component of hadith scholarship but also constitutes an epistemological basis for assessing the authenticity, validity, and authority of religious information. This study employed a qualitative approach with a case study design. Data were collected through in-depth interviews with Al-Qur’an and Hadith teachers from Madrasah Aliyah in Kediri. The findings indicate that teachers generally perceive sanad as essential for verifying the authenticity of hadith and establishing responsible religious knowledge. Sanad is also understood as an epistemological framework that cultivates students’ critical thinking, accuracy, academic responsibility, and awareness of scholarly authority. In practice, teachers employ conceptual explanations, analysis of narrators’ credibility, sanad tracing, contextual examples, and digital media to facilitate learning. The study also identifies several challenges, including limited instructional time, inadequate references and learning media, and students’ varying prior knowledge and motivation. Despite these constraints, sanad-based learning contributes to strengthening hadith literacy and students’ capacity to critically verify religious information in the digital era.